Prognostic factors associated with achieving total oral diet after glossectomy with microvascular free tissue transfer reconstruction. (May 2019) - Chen, Diane W.; Wang, Tao; Shey-Sen Ni, Jonathan; Sandulache, Vlad C.; Graboyes, Evan M.; Worley, Mitchell; Hornig, Joshua D.; Skoner, Judith M.; Day, Terry A.; Huang, Andrew T.
Highlights: About half of patients achieve a total oral diet after MVFTT reconstruction following glossectomy. Resections of subtotal glossectomy or greater have worse total oral achievement. Forearm-based free flaps had superior outcomes but may be surrogate marker for resection extent. Normal or low BMI, prior radiation, and adjuvant chemoradiation were negative prognostic factors. Abstract: Objective: Primary surgery followed by adjuvant therapy is the current standard of care in the multidisciplinary management of squamous cell carcinoma (SCC) of the oral tongue. Additionally, salvage glossectomy is used to treat recurrent base of tongue SCC. Microvascular free tissue transfer reconstruction (MVFTT) is utilized to maximize functional outcomes such as swallowing. We sought to identify prognostic factors related to achievement of a total oral diet in patients that underwent glossectomy with MVFTT. Methods: Retrospective review at a tertiary care center from 2010 to 2015. Results: 200 patients (69% male, mean age 60 years) met inclusion criteria. Extent of glossectomy was categorized as partial or hemiglossectomy (39%), tongue base resection with or without hemi-oral glossectomy (23%), composite resection with mandibulectomy (18%), and subtotal or total glossectomy (21%). Flap success rate was 96%. Median follow-up time was 14  months. A total oral diet was achieved by 49% of patients with median time to achievement of 31  days (IQR 9-209). Multivariate analysis identified body mass index  < 25 kg/m 2, prior radiation therapy, adjuvant chemoradiation, and resection requiring subtotal or total glossectomy or concurrent mandibulectomy as independent risk factors for worse total oral diet achievement. Conclusion: Swallowing dysfunction represents a significant morbidity following glossectomy in the treatment of SCC. High BMI, smaller resection fields, and absence of prior radiation therapy or adjuvant chemoradiotherapy correlated with improved likelihood of obtaining a total oral diet. Patients should be appropriately counseled of this risk with emphasis placed on aggressive swallow rehabilitation in the post- treatment setting.